Digital Financial Ecosystems and MSME Growth in Indonesia: A Post-Pandemic Analysis - Matriadi , Faisal (KRIEZ ACADEMY : Journal of development and community service, 2024)
This study explores the profound influence of a rapidly evolving digital financial ecosystem on the growth, resilience, and sustainability of micro, small, and medium enterprises (MSMEs) in Indonesia during the post-pandemic era. The COVID-19 pandemic exposed critical vulnerabilities within the MSME sector, particularly its limited access to formal finance and its low level of digital readiness. In response, a dynamic digital financial ecosystem—encompassing digital payment systems, fintech innovations, online lending platforms, and digital bookkeeping applications—has emerged as a crucial catalyst for recovery and growth. Through a mixed-methods research design that combines a quantitative survey of 300 MSMEs across key regions with in-depth interviews of 20 stakeholders, this paper empirically examines how digital financial services enhance access to capital, improve operational efficiency, and accelerate the formalization of businesses. The findings indicate that MSMEs utilizing fintech platforms experienced a significant increase in working capital and profitability, and were more likely to join government support programs. The study concludes that the digital financial ecosystem plays a transformative role in fostering inclusive growth and long-term resilience for Indonesian MSMEs. However, to scale these benefits nationally, robust policy support for digital literacy, cybersecurity, and infrastructure development is essential, underpinned by strengthened collaborative models among fintech providers, the government, and MSME associations.